2021
DOI: 10.1037/tps0000282
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing virtual reality for disaster mental health: A systematic review.

Abstract: Widespread disasters, such as hurricanes, terrorist attacks, and viral outbreaks, represent a unique class of stressors that increase the demand for mental health care but also limit access to services. During the course of COVID-19, an unprecedented global pandemic, the detrimental effects of fear, uncertainty, and social isolation have particularly strained existing structures for psychological care. Virtual reality (VR) represents a promising means to address this still-growing need. Although VR has been ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Telepresence facilitates gestures and body language like in-person interactions while also isolating users' visual and auditory experience to the virtual environment. The immersive characteristics of VR make it an ideal solution to some common barriers of standard TMH (Boydstun et al, 2021;Di Carlo et al, 2021;Matamala-Gomez et al, 2021;Pimentel et al, 2021;Sampaio et al, 2021).…”
Section: Benefits Of Vret + Tmhmentioning
confidence: 99%
“…Telepresence facilitates gestures and body language like in-person interactions while also isolating users' visual and auditory experience to the virtual environment. The immersive characteristics of VR make it an ideal solution to some common barriers of standard TMH (Boydstun et al, 2021;Di Carlo et al, 2021;Matamala-Gomez et al, 2021;Pimentel et al, 2021;Sampaio et al, 2021).…”
Section: Benefits Of Vret + Tmhmentioning
confidence: 99%
“…Additionally, VR interventions demonstrated effectiveness in case of natural disasters. VR-based interventions effectively alleviated PTSD symptoms, anxiety, and depression caused by natural disasters [ 31 , 32 ]. Metaanalysis studies have shown moderate to large effects of VR interventions compared to control conditions for anxiety and depression outcomes (e.g., waitlist, placebo, relaxation, and treatment as usual) [ 33 ], and a large effect size for VR therapy on anxiety disorders, which was comparable to in vivo conditions [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…VR-based interventions effectively alleviated PTSD symptoms, anxiety, and depression caused by natural disasters. 31,32 Metaanalysis studies have shown moderate to large effects of VR interventions compared to control conditions for anxiety and depression outcomes (e.g., waitlist, placebo, relaxation, and treatment as usual), 33 and a large effect size for VR therapy on anxiety disorders, which was comparable to in vivo conditions. 34 Prior studies revealed the potential of digital therapeutic technology like as immersive VR that offer cost-effective, scalable, and on-demand solution to address mental problems.…”
mentioning
confidence: 99%
“…Finally, Boydstun et al (2021) present a systematic review of research on the acceptability, feasibility, and efficacy of VR interventions in the context of disasters. They review documents VR’s promise in this area, and may serve to encourage the development of modern VR interventions and large-scale studies to address this highly relevant societal need.…”
mentioning
confidence: 99%